1997
DOI: 10.1101/gad.11.19.2468
|View full text |Cite
|
Sign up to set email alerts
|

K-ras is an essential gene in the mouse with partial functional overlap with N-ras

Abstract: Mammalian ras genes are thought to be critical in the regulation of cellular proliferation and differentiation and are mutated in ∼30% of all human tumors. However, N-ras and H-ras are nonessential for mouse development. To characterize the normal role of K-ras in growth and development, we have mutated it by gene targeting in the mouse. On an inbred genetic background, embryos homozygous for this mutation die between 12 and 14 days of gestation, with fetal liver defects and evidence of anemia. Thus, K-ras is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
397
3
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(422 citation statements)
references
References 58 publications
15
397
3
7
Order By: Relevance
“…Moreover, it is possible that distinct mammalian Ras (H-Ras, K-Ras, N-Ras) proteins and/or Ras mutants (for example, positions 12,13,61) may di er in their ability to recognize and activate downstream targets, resulting in di erential signaling . For example, gene targeting studies indicate an essential role for Kras, but not H-or N-Ras, for normal development in mice (Koera et al, 1997;Johnson et al, 1997). This data, taken together with earlier observations that KRas-4B possesses distinct carboxy terminus modifications (James et al, 1995) and the speci®c association of KRas4B with smg-GDP dissociation stimulator (GEF) (Mizuno et al, 1991), suggests that K-Ras may have speci®c functions in signal transduction not shared by other family members.…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 82%
“…Moreover, it is possible that distinct mammalian Ras (H-Ras, K-Ras, N-Ras) proteins and/or Ras mutants (for example, positions 12,13,61) may di er in their ability to recognize and activate downstream targets, resulting in di erential signaling . For example, gene targeting studies indicate an essential role for Kras, but not H-or N-Ras, for normal development in mice (Koera et al, 1997;Johnson et al, 1997). This data, taken together with earlier observations that KRas-4B possesses distinct carboxy terminus modifications (James et al, 1995) and the speci®c association of KRas4B with smg-GDP dissociation stimulator (GEF) (Mizuno et al, 1991), suggests that K-Ras may have speci®c functions in signal transduction not shared by other family members.…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 82%
“…All cells use Ras signaling to some extent, so it is not surprising that perturbation in Ras signaling could have developmental consequences. Although all proteins are widely expressed, KRAS is ubiquitously expressed in almost all cell types and shown to be vital for normal mouse development [Johnson et al, 1997]. In contrast, mouse model studies have demonstrated HRAS and NRAS are not as critical [Malumbres and Barbacid, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, K-ras knockout mice die at 12.5 days post coitus (p.c.) from severe anemia (Johnson et al, 1997;Koera et al, 1997). Ras isoforms differ with respect to post-translational modifications, subcellular localization and transformation properties (Hingorani and Tuveson, 2003).…”
Section: Discussionmentioning
confidence: 99%